Examining pre-service science teachers' development and utilization of written and oral argument and representation resources in an argument-based inquiry environment. Issue 4 (10th August 2022) - Yaman, Fatma; Hand, Brian
Abstract : This study investigated the development and utilization of argument and representation resources in pre-service science teachers' (PSTs') written and oral arguments over two semesters in an argument-based inquiry environment of General Chemistry Laboratory I and II courses. The study employed a form of mixed methods research that is known as 'data-transformation variant of convergent design' which allows quantification of qualitative data. Data sources included PSTs' 180 laboratory reports and 20 video recordings. A Friedman test and a Spearman-Brown correlation were conducted for statistical analysis. The results revealed that the quality of argument and representation were intertwined in both written and oral argumentation. While the PSTs' quality of written argument and representation significantly increased from the first-time phase to the following time phases, in oral argumentation the quality remained stable after the second time phase. There was also a positive correlation amongst the PSTs' quality of written and oral argument and representation. The PSTs' representational competency increased over time and they connected more representations in written arguments. The results suggest that students should be provided with opportunities to engage in sustained talking, writing, and reading practices both publicly and privately in order to critique and construct arguments, develop representational competency, and integrate ideas.